A phase 2 safety study of accelerated elotuzumab infusion, over less than 1 h, in combination with lenalidomide and dexamethasone, in patients with multiple myeloma. Issue 5 (22nd March 2017) - Berenson, James; Manges, Robert; Badarinath, Suprith; Cartmell, Alan; McIntyre, Kristi; Lyons, Roger; Harb, Wael; Mohamed, Hesham; Nourbakhsh, Ali; Rifkin, Robert
Abstract: Elotuzumab, an immunostimulatory SLAMF7‐targeting monoclonal antibody, induces myeloma cell death with minimal effects on normal tissue. In a previous phase 3 study in patients with relapsed/refractory multiple myeloma (RRMM), elotuzumab (10 mg/kg, ∼3‐h infusion), combined with lenalidomide and dexamethasone, demonstrated durable efficacy and acceptable safety; 10% (33/321) of patients had infusion reactions (IRs; Grade 1/2: 29; Grade 3: 4). This phase 2 study (NCT02159365) investigated an accelerated infusion schedule in 70 patients with newly diagnosed multiple myeloma or RRMM. The primary endpoint was cumulative incidence of Grade 3/4 IRs by completion of treatment Cycle 2. Dosing comprised elotuzumab 10 mg/kg intravenously (weekly, Cycles 1‐2; biweekly, Cycles 3+), lenalidomide 25 mg (daily, Days 1‐21), and dexamethasone (28 mg orally and 8 mg intravenously, weekly, Cycles 1‐2; 40 mg orally, weekly, Cycles 3+), in 28‐day cycles. Premedication with diphenhydramine, acetaminophen, and ranitidine (or their equivalents) was given as in previous studies. If no IRs occurred, infusion rate was increased in Cycle 1 from 0.5 to 2 mL/min during dose 1 (∼2 h 50 min duration) to 5 mL/min for the entire infusion by dose 3 and also during all subsequent infusions (∼1‐h duration). Median number of treatment cycles was six. No Grade 3/4 IRs occurred; only one Grade 1 and one Grade 2 IR occurred, both during the first infusion. These data support the safety of a faster infusion of elotuzumab administered over ∼1 h by the third dose, providing a more convenient alternative dosing option for patients.